ASSESSING THE DEGREE OF PROMPTNESS OF A SERVICE INDUSTRY TO ADOPT LEAN THINKING - Sellitto, Miguel Afonso; Borchardt, Miriam; Medeiros Pereira, Giancarlo (Revista Eletrônica de Administração, 2013)
This paper describes the development and implementation of an index able to assess the degree of promptness of a service industry to carry out procedures towards lean thinking. According to the measurements theory and multivariate statistics, an approach to modelling lean thinking is developed. Starting with a theoretical review of concepts, one is able to devise a model making use of appropriate techniques for assessing manifested variables with questionnaires. The application of the model is expected to lead to a treelike structure representing the phenomenon with unitary prediction coefficients linearly combined. The Crombach´s alpha is employed in testing the reliability of the measurements. Non-linear or circular structures are out of the scope of this paper. The model is then applied to the public transportation industry of the City of Porto Alegre, Brazil, where the degree of promptness to adopt lean thinking in the industry as a whole and in the fifteen member companies has been assessed. The results are discussed and suggestions for pursuing the research are presented.